The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1089/ten.teb.2011.0603
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Tendon and Ligament Healing: Opportunities with Recombinant Human Platelet-Derived Growth Factor BB-Homodimer

Abstract: Intrinsic tendon healing in response to injury is a reparative process that often results in formation of scar tissue with functional and mechanical properties inferior to those of the native tendon. Development of therapies that can promote regenerative, rather than reparative, healing hold the promise of improving patient recovery from tendon and ligament injuries by producing tissue that is morphologically and functionally equivalent to the native tissue. One therapeutic approach that has been a frequent to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 102 publications
0
25
0
Order By: Relevance
“…The morphologic results were confirmed by the serum PDGF level. Positive correlation between the PDGF level and quality of the healing response and higher values of hydroxyproline has previously been reported [49]. Hee et al [49] showed that this growth factor is chemotactic, mitogenic, and pro-angiogenic.…”
Section: Discussionmentioning
confidence: 75%
“…The morphologic results were confirmed by the serum PDGF level. Positive correlation between the PDGF level and quality of the healing response and higher values of hydroxyproline has previously been reported [49]. Hee et al [49] showed that this growth factor is chemotactic, mitogenic, and pro-angiogenic.…”
Section: Discussionmentioning
confidence: 75%
“…These beneficial results may also be due to the role of PDGFs [21,36]. Zhang and Wang [37] showed that PRPclot releasate, due to its growth factors, promotes differentiation of tendon stem cells into active tenocytes, exhibiting high proliferation rates and collagen production capability.…”
Section: Discussionmentioning
confidence: 99%
“…Various forms of platelets such as platelet-rich plasma, platelet fibrin glue or platelet gel and direct injection of pure platelets have been used to accelerate tendon healing in vivo [13][14][15][16][17][18]. Currently, platelets are the focus of many studies due to their growth factors [19][20][21]. Recent studies suggest that the healing efficacy of the platelets could be due to their ability to induce inflammation, which is important for tendon healing [13,16,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review, Hee et al 39 stated that PDGF-BB is chemotactic, mitogenic, and pro-angiogenic. It regulates proliferation of tendon cells and induces extracellular matrix deposition and organization.…”
mentioning
confidence: 99%